Coalescence formation of muonic atoms at RHIC - Xiaofeng Wang; Frank Geurts; Zebo Tang; Kefeng Xin; Zhangbu Xu; Yifei Zhang; Long Zhou (Physics Letters B)
The discovery of exotic muonic atoms, including antimatter hydrogen muonic atoms and kaon muonic atoms, constitutes a milestone in our ability to make and study new forms of matter. Relativistic heavy-ion collisions provide the only likely condition for production and detection of these exotic atoms. Taking Coulomb correlations into account from the time of the fireball freeze-out, which refers to the cessation of hadronic interactions in the high-temperature, high-density region formed after the collision, until the formation of a stable atom has dramatic consequences on the expected yields of these atoms. When the coalescence model with the assumption of quantum wave function localization is applied to the formation of muonic atoms, we find that the atom yields are about two orders of magnitude higher than previously predicted.